Developing brains and changing worlds: Macroenvironmental changes and their association with brain development - Juan F. Quinones; Tobias Banaschewski; Arun L.W. Bokde; Sylvane Desrivières; Herta Flor; Hugh Garavan; Penny Gowland; Antoine Grigis; Andreas Heinz; Herve Lemaitre; Jean-Luc Martinot; Marie-Laure Paillère Martinot; et al. (Environmental Research, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Prioritising domestic locations for marine biosecurity management within a regional vessel network - Cal Faubel; Oliver Floerl; Kyle Hilliam; Simone L Stevenson; Eric A Treml (Biological Conservation, 2025)

Borealisation of Plant Communities in the Arctic Is Driven by Boreal‐Tundra Species - Mariana García Criado; Isabel C. Barrio; James D. M. Speed; Anne D. Bjorkman; Sarah C. Elmendorf; Isla H. Myers‐Smith; Rien Aerts; Juha M. Alatalo; Katlyn R. Betway‐May; Robert G. Björk; Mats P. Björkman; Daan Blok; et al. (Ecology Letters, 2025)
Following rapid climate change, tundra plant communities are experiencing extensive compositional shifts. A conservation concern is the potential encroachment of boreal species into the tundra (‘borealisation’). Tundra borealisation has been sporadically reported, but not systematically quantified. Here, we synthesised data from across 32 study areas, spanning 1137 plots and 287 vascular plant species, resurveyed between 1981 and 2023. We (i) quantified tundra borealisation as the colonisation and increase in abundance of Boreal and Boreal‐Tundra species, (ii) assessed biogeographical, climatic and local borealisation drivers and (iii) identified species contributing to borealisation and their associated traits. Half of the plots experienced borealisation, although borealisation rates were not different to random expectation. Borealisation was greater in Eurasia, closer to the treeline, at higher elevations, in warmer and wetter regions, where climate change was limited, and where initial boreal abundance was lower. Boreal coloniser species were generally short‐statured, and more often shrubs and graminoids. Boreal species colonised around three times less frequently than Boreal‐Tundra species. Hence, our findings indicate that tundra borealisation is mainly driven by the spread of already established boreal‐low Arctic tundra species. These plant community composition changes could have cascading impacts on land‐atmosphere interactions, trophic dynamics and Indigenous and local livelihoods.

Seasonal synchrony between vessel arrivals and larval production may influence the likelihood of biofouling introductions - Simone L. Stevenson; Ian Davidson; Julio Botero; Kay Critchell; Cal Faubel; Kyle Hilliam; Oliver Floerl; Melissa Welsh; Eric A. Treml (Biological Invasions, 2025)
Biofouling of ships and boats is a dominant global transport pathway for marine invasive species. Many biofouling non-indigenous species (NIS) can only be entrained by vessels and subsequently ‘discharged’ during the short-lived but highly mobile larval stage. This means their introduction to new locations is reliant on vessels arriving in suitable habitat while biofouling adults on the hull are spawning. Vessel arrivals and spawning are, however, both transient events. The influence of synchrony between shipping traffic and spawning on introductions of marine NIS is not well understood. Using New Zealand as a case study, we show that seasonality of domestic vessel arrivals is much more prevalent than for international vessel arrivals. Seasonality was identified in 35 of 58 nationwide locations receiving commercial maritime traffic. Seasonal locations most commonly experienced their shipping peaks during spring and summer, while troughs were most common during winter and autumn. This seasonal pattern produces more opportunities for introductions of spring–summer spawners, while potentially limiting introductions of autumn and winter spawners around New Zealand. Our findings indicate the importance of incorporating seasonality into models and risk-assessments of vessel-mediated incursions, and the need for more empirical data on the timing of introduction and entrainment events. There may be an opportunity to optimise surveillance and vector management efforts during periods of peak synchronicity, where the likelihood of incursions is higher.

Clinical efficacy of a parasiticide formulation containing eprinomectin, esafoxolaner and praziquantel (NexGard® Combo) in the treatment of natural feline aelurostrongylosis and troglostrongylosis - Angela Di Cesare; Fabrizia Veronesi; Paolo Emidio Crisi; Mariasole Colombo; Simone Morelli; Massimo Vignoli; Giulia Rigamonti; Raffaella Iorio; Eric Tielemans; Frederic Beugnet; Camille Gamblin; Donato Traversa (Veterinary Parasitology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Corrigendum to “Lizards in the wind: The impact of wind on the thermoregulation of the common wall lizard” [J. Therm. Biol. 121 (2024) 103855] - Sierra Spears; Ciara Pettit; Sophie Berkowitz; Simone Collier; Cece Colwell; Ethan H. Livingston; Wyatt McQueen; Princeton L. Vaughn; Brooke L. Bodensteiner; Vianey Leos-Barajas; Eric J. Gangloff (Journal of Thermal Biology, 2024)

Lizards in the wind: The impact of wind on the thermoregulation of the common wall lizard - Sierra Spears; Ciara Pettit; Sophie Berkowitz; Simone Collier; Cece Colwell; Ethan H. Livingston; Wyatt McQueen; Princeton L. Vaughn; Brooke L. Bodensteiner; Vianey Leos-Barajas; Eric J. Gangloff (Journal of Thermal Biology, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

River–coastal–ocean continuum modeling along the Lazio coast (Tyrrhenian Sea, Italy): Assessment of near river dynamics in the Tiber delta - Simone Bonamano; Ivan Federico; Salvatore Causio; Viviana Piermattei; Daniele Piazzolla; Sergio Scanu; Alice Madonia; Nicola Madonia; Giovanni De Cillis; Eric Jansen; Giorgio Fersini; Giovanni Coppini; et al. (Estuarine, Coastal and Shelf Science, 2024)

Temperature alters the toxicological impacts of plant terpenoids on the polyphagous model herbivore Vanessa cardui - Mari R. Irving; Eric W. Goolsby; Hannah Stanford; Simone Lim-Hing; Maria Urrea; Chase M. Mason (Journal of Chemical Ecology, 2023)
Terpenes are a major class of secondary metabolites present in all plants, and long hypothesized to have diversified in response to specific plant-herbivore interactions. Herbivory is a major biotic interaction that plays out across broad temporal and spatial scales that vary dramatically in temperature regimes, both due to climatic variation across geographic locations as well as the effect of seasonality. In addition, there is an emerging understanding that global climate change will continue to alter the temperature regimes of nearly every habitat on Earth over the coming centuries. Regardless of source, variation in temperature may influence herbivory, in particular via changes in the efficacy and impacts of plant defensive chemistry. This study aims to characterize temperature-driven variation in toxicological effects across several structural classes of terpenes in the model herbivore Vanessa cardui , the painted lady butterfly. We observed a general increase in monoterpene toxicity to larvae, pupa, and adults at higher temperatures, as well as an increase in development time as terpene concentration increased. Results obtained from this study yield insights into possible drivers of seasonal variation in plant terpene production as well as inform effects of rising global temperatures on plant-insect interactions. In the context of other known effects of climate change on plant-herbivore interactions like carbon fertilization and compensatory feeding, temperature-driven changes in plant chemical defense efficacy may further complicate the prediction of climate change impacts on the fundamental ecological process of herbivory.

From Early Bronze Age domestic plant production to Middle Bronze Age regional exchange economy: the archaeobotanical assemblages from Tel Kabri - Marco Nicoli’; Simone Riehl; Eric H. Cline; Assaf Yasur-Landau (Archaeological and Anthropological Sciences, 2023)
Recent excavations at the site of Tel Kabri have brought some extraordinary findings, including the earliest wine cellar in the ancient Near East discovered in 2013. During these excavations, archaeobotanical samples were collected continuously and then processed in 2019. The archaeobotanical studies focus on the Middle Bronze Age palace in Area DW and the Early Bronze Age domestic deposits in Area L. The results confirm the different nature of the two contexts. Legumes form a large portion of the crop remains in the Early Bronze Age Area L: Lathyrus sativus (grass pea), Vicia faba var. minor (faba bean), and Lens culinaris (lentil), all showing no drought stress and similar growing conditions in terms of moisture availability, as indicated by stable carbon isotope measurements. For Area L, several wild seeds have been identified to represent weeds of cereal crops, whereas Area DW is strongly affected by small wild seeds that entered the sediments as modern contaminants. Fruit crops are present in both assemblages with Olea europaea (olive), representing the most ubiquitous taxon, and Vitis vinifera (grape), with most of its pips found mineralized. The identified remains also include cereal crops, primarily Triticum dicoccum (emmer), which appears cultivated under exceptionally dry conditions. The stable nitrogen values for emmer also raised some questions regarding the growing location and cultivation strategy. Correspondence analysis has been applied, comparing the archaeobotanical assemblages of Tel Kabri within the wider geographical and chronological Levantine context and determining their placement in sub-regional patterns.

Phenolic profiles and their responses to pre- and post-harvest factors in small fruits: a review - Yifan Yan; Joana Pico; Bohan Sun; Anubhav Pratap-Singh; Eric Gerbrandt; Simone Diego Castellarin (Critical Reviews in Food Science and Nutrition, 2023)

Demystifying image-based machine learning: a practical guide to automated analysis of field imagery using modern machine learning tools - Byron T. Belcher; Eliana H. Bower; Benjamin Burford; Maria Rosa Celis; Ashkaan K. Fahimipour; Isabela L. Guevara; Kakani Katija; Zulekha Khokhar; Anjana Manjunath; Samuel Nelson; Simone Olivetti; Eric Orenstein; et al. (Frontiers in Marine Science, 2023)
Image-based machine learning methods are becoming among the most widely-used forms of data analysis across science, technology, engineering, and industry. These methods are powerful because they can rapidly and automatically extract rich contextual and spatial information from images, a process that has historically required a large amount of human labor. A wide range of recent scientific applications have demonstrated the potential of these methods to change how researchers study the ocean. However, despite their promise, machine learning tools are still under-exploited in many domains including species and environmental monitoring, biodiversity surveys, fisheries abundance and size estimation, rare event and species detection, the study of animal behavior, and citizen science. Our objective in this article is to provide an approachable, end-to-end guide to help researchers apply image-based machine learning methods effectively to their own research problems. Using a case study, we describe how to prepare data, train and deploy models, and overcome common issues that can cause models to underperform. Importantly, we discuss how to diagnose problems that can cause poor model performance on new imagery to build robust tools that can vastly accelerate data acquisition in the marine realm. Code to perform analyses is provided at https://github.com/heinsense2/AIO_CaseStudy .

Poriferans rift apart: molecular demosponge biodiversity in Central and French Polynesia and comparison with adjacent marine provinces of the Central Indo-Pacific - Adrian Galitz; Merrick Ekins; Eric Folcher; Gabriele Büttner; Kathryn Hall; John N. A. Hooper; Maggie M. Reddy; Simone Schätzle; Olivier P. Thomas; Gert Wörheide; Sylvain Petek; Cécile Debitus; et al. (Biodiversity and Conservation, 2023)
The distribution of marine sponges in the tropical Southwest Pacific Ocean is largely unexplored despite the vital ecological role of sponges in coral reefs and their value as sources of metabolites for drug design. Several collection campaigns to the French Polynesian archipelagos (Society, Marquesas, Tuamotu, Gambier, and Austral) were conducted to assess the bio- and chemodiversity of the island groups. In the course of these scientific expeditions, more than 200 identified sponge specimens were acquired, for which we were able to assign 102 Molecular Operational Taxonomic Units (MOTUs). Based on these MOTUs, we assessed, in the largest analysis of its kind for this area to date, the sponge composition and faunistic overlaps of the marine province Southeast Polynesia with Marquesas and Central Polynesia. We also compared the sponge fauna of these Eastern Indo-Pacific provinces with marine provinces of the adjacent Central Indo-Pacific realm. Our findings corroborate that sponge faunal similarity within marine realms is higher than among realms, and follows the marine barriers to gene flow observed for other taxa. We detected high levels of provincial endemism for marine sponges, consistent with findings from other Indo-Pacific regions. At the level of province, geographical distance and ocean surface currents influence faunal similarity, and constitute the primary factors for the connectivity of sponge faunas between the disjunct and remote island groups in the tropical Southwest Pacific Ocean.

Comprehensive anthocyanin and flavonol profiling and fruit surface color of 20 blueberry genotypes during postharvest storage - Yifan Yan; Joana Pico; Eric M. Gerbrandt; Michael Dossett; Simone D. Castellarin (Postharvest Biology and Technology, 2023)

A pragmatic authenticity assessment of lemon (Citrus limon [L.] Burm.f.) juices by its profile of coumarins, psoralens, and polymethoxyflavones - Markus Jungen; Nenad Dragićević; Miriam Rodriguez-Werner; Simone Schmidt; Katy Dinis; Lucie Tsamba; Eric Jamin; Thorsten Fiedler; Nadine Fischbach; Christof B. Steingass; Valérie Camel; Ralf Schweiggert (Food Control, 2023)

Determination of bound volatiles in blueberries, raspberries, and grapes with an optimized protocol and a validated SPME-GC/MS method - Joana Pico; Kimia Nozadi; Eric M. Gerbrandt; Michael Dossett; Simone D. Castellarin (Food Chemistry, 2023)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

The legacy of predator threat shapes prey foraging behaviour - Simone Des Roches; Rebecca R. Robinson; Michael T. Kinnison; Eric P. Palkovacs (Oecologia, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Human astrovirus types 1, 4 and 5 circulating among children with acute gastroenteritis in a rural Brazilian state, 2010-2016 - Adriana Luchs; Kaelan Tardy; Roozbeh Tahmasebi; Simone Guadagnucci Morillo; Flavio Augusto de Pádua Milagres; Vanessa dos Santos Morais; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Lais Sampaio de Azevedo; Ellen Viana de Souza; Roberta Salzone Medeiros; Yasmin França Viana Pires de Souza; et al. (Archives of Virology, 2021)

Path Planning for Underwater Information Gathering Based on Genetic Algorithms and Data Stochastic Models - Matteo Bresciani; Francesco Ruscio; Simone Tani; Giovanni Peralta; Andrea Timperi; Eric Guerrero-Font; Francisco Bonin-Font; Andrea Caiti; Riccardo Costanzi (Journal of Marine Science and Engineering, 2021)
Recent technological developments have paved the way to the employment of Autonomous Underwater Vehicles (AUVs) for monitoring and exploration activities of marine environments. Traditionally, in information gathering scenarios for monitoring purposes, AUVs follow predefined paths that are not efficient in terms of information content and energy consumption. Informative Path Planning (IPP) represents a valid alternative, defining the path that maximises the gathered information. This work proposes a Genetic Path Planner (GPP), which consists in an IPP strategy based on a Genetic Algorithm, with the aim of generating a path that simultaneously maximises the information gathered and the coverage of the inspected area. The proposed approach has been tested offline for monitoring and inspection applications of Posidonia Oceanica (PO) in three different geographical areas. The a priori knowledge about the presence of PO, in probabilistic terms, has been modelled utilising a Gaussian Process (GP), trained on real marine data. The GP estimate has then been exploited to retrieve an information content of each position in the areas of interest. A comparison with other two IPP approaches has been carried out to assess the performance of the proposed algorithm.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Climate‐driven habitat change causes evolution in Threespine Stickleback - Simone Des Roches; Michael A. Bell; Eric P. Palkovacs (Global Change Biology, 2020)
Climate change can shape evolution directly by altering abiotic conditions or indirectly by modifying habitats, yet few studies have investigated the effects of climate‐driven habitat change on contemporary evolution. We resampled populations of Threespine Stickleback ( Gasterosteus aculeatus ) along a latitudinal gradient in California bar‐built estuaries to examine their evolution in response to changing climate and habitat. We took advantage of the strong association between stickleback lateral plate phenotypes and Ectodysplasin A ( Eda ) genotypes to infer changes in allele frequencies over time. Our results show that over time the frequency of low‐plated alleles has generally increased and heterozygosity has decreased. Latitudinal patterns in stickleback plate phenotypes suggest that evolution at Eda is a response to climate‐driven habitat transformation rather than a direct consequence of climate. As climate change has reduced precipitation and increased temperature and drought, bar‐built estuaries have transitioned from lotic (flowing‐water) to lentic (still‐water) habitats, where the low‐plated allele is favoured. The low‐plated allele has achieved fixation at the driest, hottest southernmost sites, a trend that is progressing northward with climate change. Climate‐driven habitat change is therefore causing a reduction in genetic variation that may hinder future adaptation for populations facing multiple threats.

The Global High Frequency Radar Network - Hugh Roarty; Thomas Cook; Lisa Hazard; Doug George; Jack Harlan; Simone Cosoli; Lucy Wyatt; Enrique Alvarez Fanjul; Eric Terrill; Mark Otero; John Largier; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Deciphering the worldwide invasion of the Asian long‐horned beetle: A recurrent invasion process from the native area together with a bridgehead effect - Marion Javal; Eric Lombaert; Tetyana Tsykun; Claudine Courtin; Carole Kerdelhué; Simone Prospero; Alain Roques; Géraldine Roux (Molecular Ecology, 2019)
Retracing introduction routes is crucial for understanding the evolutionary processes involved in an invasion, as well as for highlighting the invasion history of a species at the global scale. The Asian long‐horned beetle (ALB) Anoplophora glabripennis is a xylophagous pest native to Asia and invasive in North America and Europe. It is responsible for severe losses of urban trees, in both its native and invaded ranges. Based on historical and genetic data, several hypotheses have been formulated concerning its invasion history, including the possibility of multiple introductions from the native zone and secondary dispersal within the invaded areas, but none have been formally tested. In this study, we characterized the genetic structure of ALB in both its native and invaded ranges using microsatellites. In order to test different invasion scenarios, we used an approximate Bayesian “random forest” algorithm together with traditional population genetics approaches. The strong population differentiation observed in the native area was not geographically structured, suggesting complex migration events that were probably human‐mediated. Both native and invasive populations had low genetic diversity, but this characteristic did not prevent the success of the ALB invasions. Our results highlight the complexity of invasion pathways for insect pests. Specifically, our findings indicate that invasive species might be repeatedly introduced from their native range, and they emphasize the importance of multiple, human‐mediated introductions in successful invasions. Finally, our results demonstrate that invasive species can spread across continents following a bridgehead path, in which an invasive population may have acted as a source for another invasion.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Indirect somatic embryogenesis of Theobroma cacao L. in liquid medium and improvement of embryo-to-plantlet conversion rate - Caroline Guillou; Audrey Fillodeau; Eric Brulard; David Breton; Simone De Faria Maraschin; Dorothée Verdier; Mathieu Simon; Jean-Paul Ducos (In Vitro Cellular & Developmental Biology - Plant, 2018)

Resurrection and emendation of the Hypoxylaceae, recognised from a multigene phylogeny of the Xylariales - Lucile Wendt; Esteban Benjamin Sir; Eric Kuhnert; Simone Heitkämper; Christopher Lambert; Adriana I. Hladki; Andrea I. Romero; J. Jennifer Luangsa-ard; Prasert Srikitikulchai; Derek Peršoh; Marc Stadler (Mycological Progress, 2018)

Coarse muscovite veins and alteration deep in the Yerington batholith, Nevada: insights into fluid exsolution in the roots of porphyry copper systems - Simone E. Runyon; Matthew Steele-MacInnis; Eric Seedorff; Pilar Lecumberri-Sanchez; Frank K. Mazdab (Mineralium Deposita, 2017)

Characterizing the Natural System: Toward Sustained, Integrated Coastal Ocean Acidification Observing Networks to Facilitate Resource Management and Decision Support - Simone Alin; Russell Brainard; Nichole Price; Jan Newton; Anne Cohen; William Peterson; Eric DeCarlo; Elizabeth Shadwick; Scott Noakes; Nina Bednaršek (Oceanography, 2015)

Interactions between repeated fire, nutrients, and insect herbivores affect the recovery of diversity in the southern Amazon - Tara Joy Massad; Jennifer K. Balch; Eric A. Davidson; Paulo M. Brando; Cândida Lahís Mews; Pábio Porto; Raimundo Mota Quintino; Simone A. Vieira; Ben Hur Marimon Junior; Susan E. Trumbore (Oecologia, 2013)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Pharmacokinetics and protein binding of cefazolin in morbidly obese patients - Simone van Kralingen; Margot Taks; Jeroen Diepstraten; Ewoudt M. van de Garde; Eric P. van Dongen; Marinus J. Wiezer; Bert van Ramshorst; Bart Vlaminckx; Vera H. Deneer; Catherijne A. Knibbe (European Journal of Clinical Pharmacology, 2011)

Stimulant effects of adenosine antagonists on operant behavior: differential actions of selective A2A and A1 antagonists - Patrick A. Randall; Eric J. Nunes; Simone L. Janniere; Colin M. Stopper; Andrew M. Farrar; Thomas N. Sager; Younis Baqi; Jörg Hockemeyer; Christa E. Müller; John D. Salamone (Psychopharmacology, 2011)

Strong microsite control of seedling recruitment in tundra - Bente J. Graae; Rasmus Ejrnæs; Simone I. Lang; Eric Meineri; Pablo T. Ibarra; Hans Henrik Bruun (Oecologia, 2011)

Arsenic in the Hair of the Individuals in Santana-AP-Brazil: Significance of Residence Location - Simone de Fátima Pinheiro Pereira; Augusto Fonseca Saraiva; Maria Izabel Fernandes de Alencar; Stephen Eric Ronan; Wagner Soares de Alencar; Geiso Rafael Fonseca Oliveira; Cleber Silva e Silva; Rafaella Galvão Miranda (Bulletin of Environmental Contamination and Toxicology, 2010)

Loading PEG-Catalase into Filamentous and Spherical Polymer Nanocarriers - Eric A. Simone; Thomas D. Dziubla; Evguenia Arguiri; Vanessa Vardon; Vladimir V. Shuvaev; Melpo Christofidou-Solomidou; Vladimir R. Muzykantov (Pharmaceutical Research, 2009)

Targeted delivery of therapeutics to endothelium - Eric Simone; Bi-Sen Ding; Vladimir Muzykantov (Cell and Tissue Research, 2009)

Cancer mortality risk among biology research workers in France: first results of two retrospective cohorts studies - Irina Guseva Canu; Agnès Rogel; Eric Samson; Simone Benhamou; Agnès Laplanche; Margot Tirmarche (International Archives of Occupational and Environmental Health, 2008)

Genotypic and phenotypic characterization of six new recombinant congenic strains derived from NOD/Shi and CBA/J genomes - Peter C. Reifsnyder; Jeffry C. Flynn; Amanda L. Gavin; Eric A. Simone; John J. Sharp; Lieselotte Herberg; Edward H. Leiter (Mammalian Genome, 1999)